High prevalence of the ACSL (rs6552828) AA genotype among elite soccer players - Meckel, Y.; Eliakim, A.; Nemet, D.; Levin, N.; Ben-Zaken, S. (Baltic Journal of Sport and Health Sciences, 2022)
Background: The ACSL A/G single nucleotide polymorphism is associated with endurance trainability. It was previously demonstrated that AA carriers had a reduced maximal oxygen consumption (VO2 max) in response to training compared to GG carriers, and that this polymorphism explained 6.1% of the variance in the VO2 max response to training. The aim of the present study was to determine the prevalence of the ACSL A/G polymorphism among soccer players.